Webcam based maker tracking application - Lim, De Jiang (2011)
Touchless technology is still considered a new field in information technology due to its effectiveness in real world application.This technology started in development in the late 80s.Although this technology has been around for about 20 years,the application of this technology is not widely.This is primarily because it is only suitable for interaction between human and computer for entertainment purposes.The example we can see is the implementation of this technology is in Xbox 360 or Microsoft Kinect, which is mainly targeted in entertainment.In order to implement this technology besides for entertainment, Webcam-based Marker Tracking Application has been developed to show its usage in writing recognition.It offers an interactive and fun way of handwriting,recognition by using marker tracking.In addition,the low cost hardware and software requirement of this technology makes it can used by anyone.Object-oriented analysis and design method has been used in the development of this project.The way this method decompose each function into object makes it easy for problem solving.This is because we can focus on the solution on one object before continues to the next.Finally,I deeply believes Touchiess can be implemented in other field besides than entertainment,probably it can be implemented in education for children learning purposes.